(untitled) (e-Journal of Linguistics, 2025)
This study aims to analyze language errors in posts and comments on Lambe Turah’s Instagram account in 2022. This study uses the theory of language errors related to word structure proposed by Ghufron as a theoretical basis. The method used is a qualitative descriptive approach, which focuses on the analysis of data collected from the comments column on the Lambe Turah account. Data collection was carried out using the read and note method, where researchers actively read and recorded various language errors found in user comments. The main data source for this study came from various comments posted on the account during 2022. The results of the study showed that there were 37 forms of language errors identified, including errors in basic words, prefixes, clitics, reduplication, acronymization, and prepositions. This general study provides an overview of the extent of language errors that occur in communication on social media, especially on platforms like Instagram, and how variations in these forms of errors can be verified and analyzed based on linguistic theory. These findings are expected to contribute to further research in the field of linguistics, especially related to language phenomena on social media.